Мониторинг установки ЛЧ-35-11/1000 с использованием компьютерной системы контроля работы катализаторов риформинга - Костенко А. В.; Молотов К. В.; Кравцов А. В. Анатолий Васильевич; Иванчина Э. Д. Эмилия Дмитриевна; Фалеев С. А. (Томск, 2007)
Деп. в ВИНИТИ 25.04.07 № 468-В2007